Genetically engineered rice endogenous 5-enolpyruvoylshikimate-3-phosphate synthase (epsps) transgene alters phenology and fitness of crop-wild hybrid offspring - Xiao Yang (Nature Portfolio, 2017)
Abstract Genetically engineered (GE) rice endogenous epsps (5-enolpyruvoylshikimate-3-phosphate synthase) gene overexpressing EPSPS can increase glyphosate herbicide-resistance of cultivated rice. This type of epsps transgene can enhance the fecundity of rice crop-weed hybrid offspring in the absence of glyphosate, stimulating great concerns over undesired environmental impacts of transgene flow to populations of wild relatives. Here, we report the substantial alteration of phenology and fitness traits in F1-F3 crop-wild hybrid descendants derived from crosses between an epsps GE rice line and two endangered wild rice (Oryza rufipogon) populations, based on the common-garden field experiments. Under the glyphosate-free condition, transgenic hybrid lineages showed significantly earlier tillering and flowering, as well as increased fecundity and overwintering survival/regeneration abilities. In addition, a negative correlation was observed between the contents of endogenous EPSPS of wild, weedy, and cultivated rice parents and fitness differences caused by the incorporation of the epsps transgene. Namely, a lower level of endogenous EPSPS in the transgene-recipient populations displayed a more pronounced enhancement in fitness. The altered phenology and enhanced fitness of crop-wild hybrid offspring by the epsps transgene may cause unwanted environmental consequences when this type of glyphosate-resistance transgene introgressed into wild rice populations through gene flow.